Análisis demográfico con respecto a la demanda del servicio de taxi en la ciudad de Machala - Mogollon Morán, Omar David (2015)
This research was conducted in order to analyze demographic demand taxi service in the city of Machala. In which knowledge and research by different authors about the subject applied to marketing globally applied. Where each of these was of vital importance for achieving expand knowledge of the tools that have been used before and now. Performing a quantitative approach through a research tool as it is the survey of people from different sectors of the city of Machala. Taxi service every day becomes a latent need for the average urban public transport as this has a direct connection without intermediate stops between the waiting and service stations, with research results could be obtained very relevant data for this mode of transport which will serve to better know their customers and thus are able to apply a proposal to design a marketing plan for the sector of public transport mode in the city Taxi Machala, allowing improvement in customer service, both in human relationships, comfort, safety and punctuality. Which allows the acquisition of new customers and retention of its existing portfolio by providing a competitive advantage over other taxi cooperatives.